Optimizing BPJS Referral Systems: A Pathway to Equitable, Sustainable Healthcare in Indonesia - Damayanti, Nabila Ardelia; Putri, Dealonika Amanda; Napitupulu, Gladys Shevani Chilau; Kholvi, Indy Zaheera; Khairunnisa, Khairunnisa; Mustama'ah, Nadiyatus Sholatil; Rachmad, Rayhan Ramadhan Daffa Attariansyah; Putri, Serli Kusuma Dewi Dwi; Turmudi, Syifa Rabitha Alizza; Santi, Neni Fidya; Evi, Nurul (Health Frontiers: Multidisciplinary Journal for Health Professionals, 2025)
The BPJS referral system in Indonesia has been instrumental in expanding healthcare access, yet challenges such as unnecessary referrals, governance transparency, and cost inefficiencies persist. Strengthening primary healthcare infrastructure, enhancing quality control, and improving patient education are critical to optimizing the system's effectiveness. This study explores the impact of targeted interventions on BPJS referral accessibility. This study employed a systematic review approach guided by the PRISMA framework. Peer-reviewed studies published between 2019 and 2023 were identified through databases such as PubMed, Scopus, and Web of Science using terms like "BPJS referral system," "healthcare accessibility," and "governance transparency." Eligible studies focused on challenges and solutions within the BPJS referral process, including over-referrals, inter-facility coordination, and patient adherence. Quality assessments were conducted using the Cochrane Risk of Bias Tool and Newcastle-Ottawa Scale. Simulation outcomes revealed significant improvements: a 30% reduction in unnecessary referrals through enhanced puskesmas capacity, a 25% decrease in cost inefficiencies via standardized protocols, and a 40% increase in public trust due to transparent governance mechanisms. Patient education initiatives improved adherence to chronic disease programs by 35%. However, challenges such as limited ambulance availability, communication breakdowns, and staff unfamiliarity with BPJS procedures remain. The BPJS referral system can be optimized through integrated strategies, including primary care strengthening, digital tool integration, and community-based education. Addressing persistent challenges like governance transparency and resource allocation is essential for equitable healthcare access. Future research should focus on scaling digital solutions, enhancing inter-facility collaboration, and fostering patient empowerment to ensure sustainable and inclusive healthcare delivery.